Reingeniería de procesos para la empresa Mueblería Vélez de la ciudad Joya de los Sachas provincia de Orellana - Morillo Ordóñez, Lorena Cynthia (2015)
In recent years the reengineering processes within companies, has become a popular idea in organizations, although it simple advertising; o the latest fashion of the Administration? Today many organizations are involved in re-engineering initiatives, although its results are not clear. When these programs are successful performance improvement, significant benefits are obtained. However, very often, many businesses fail in achieving large expected benefits. Reengineering processes in the company, it implies significant improvements in their operation, management, examining processes and methods to improve overall business and be competitive at the present time. This work called "reengineering PROCESS FOR THE COMPANY" MUEBLERÍA VELEZ "JEWEL CITY OF SACHAS Orellana province," was the general objective "Apply reengineering business processes in the city MUEBLERIA VELEZ the Jewel of the Sacha, Orellana Province. ", in order to make a thorough study of the process of the company, which after a certain study was able to determine processes that require rethinking difficulties given that currently the company is experiencing operational problems and whose overall results are obviously improved. For information on field surveys of 15 employees and an interview were applied to the manager of the furniture company, these results allow us to observe that most of the processes used must be restructured; because it does not contain the necessary steps to execute the work efficiently, there is also duplication. each of the key processes of the company, among which were identified are: production, finance and sales; subsequently its redesign was carried out with a team, which saved time and resources used in order to achieve better performance of the activities, which is reflected on efficient customer service. With applied reengineering process of modernization of machinery for the production and improvement of finance and sales increased, which significantly improve the management of the company producing furniture. For this study was started with a collection of bibliographic information that allowed a theoretical and conceptual form to scientifically support this research framework. He then proceeded to make a situational analysis of the company Mueblería Sanchez, from which it was evident that the company has 15 employees between workers and management and its main activity was the construction of furniture in general. He is currently structured with the Executive level, level of support and operational level, serving in the Barrio's, Canton Joya de los Sachas, Orellana Province Freedom. In all raw materials processing company is like the case of furniture production is vital implementing reengineering, as it will make in less time operations, thus making better use of resources is achieved